THE INFLUENCE OF SCIENCE, TECHNOLOGY, AND SOCIETY (STS) ON STUDENT LEARNING OUTCOMES IN THE SUBCONCEPT OF GLOBAL WARMING - Mufti Ali (Institut Pendidikan Indonesia IPI Garut, 2019)
ABSTRACTThe purpose of this study is to determine the effect of science technology and society (STS) learning model on the learning outcomes of student on the sub concepts of the global warming in class VII SMP Negeri 5 Tasikmalaya.This research was conducted in December 2017 until Juni 2018 at SMP Negeri 5 Tasikmalaya. The research method used is the